Peningkatkan Kompetensi Guru Mata Pelajaran MA Masmur dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) Kurikulum 2013 melalui Workshop - Syarifah Wan (Anotero Lembaga Scientific Pekanbaru, 2022)
This research is the form of School Action Research, which is a research that is a collaboration between researchers and teachers. This study aims to improve the competence of subject teachers in preparing the Lesson Plan (RPP) through a workshop at MA Masmur. A total of 20 MA Masmur subject teachers became research subjects through workshops held at the school in two cycles. Submission of material related to the development of the Learning Implementation Plan (RPP) is carried out by the researcher who is the Head of MA Masmur. The method used in this research is descriptive method. The research procedure carried out includes the following steps; 1) planning, 2) implementation, 3) observation and 4) reflection. Data were collected through interviews, observations and reflections. The data was then analyzed using the percentage technique to see the increase that occurred from cycle 1 to cycle 2. The results of this school action research showed that in the first cycle the average value of the 2013 Curriculum RPP component developed by the teacher was 52.2%, in the second cycle the score was 52.2%. the average component of the 2013 Curriculum RPP developed by teachers was 84.4%, so there was an increase of 32.2%. The results of the School Action Research (PTS) can be concluded as follows: Through workshops it can increase teacher motivation in compiling the 2013 Curriculum RPP completely